Entrepreneurship Education and Entrepreneurial Intentions of College Students: The Mediating Role of Entrepreneurial Self-Efficacy and the Moderating Role of Entrepreneurial Competition Experience - Wu, Lihao; Jiang, Suo; Wang, Xiaomin; Yu, Linwei; Wang, Yansu; Pan, Hui (Frontiers in Psychology, 2022)
This study aims to explore effective ways to improve college students’ entrepreneurial self-efficacy and intentions through entrepreneurship education. The survey used a random sample of 804 college students in Zhejiang Province, China. The results show that: (1) In terms of the characteristics of entrepreneurial intention, there are significant differences in gender, entrepreneurial experience, entrepreneurial competition experience, and family background of self-employment. (2) There are significant differences in the characteristics of entrepreneurship education in gender, entrepreneurial competition experience, and the family background of self-employment. (3) In the relationship among entrepreneurship education, entrepreneurial self-efficacy, and entrepreneurial intention, entrepreneurship education is significantly and positively related to entrepreneurial self-efficacy and entrepreneurial intention. Entrepreneurial self-efficacy is significantly and positively associated with entrepreneurial intention. Entrepreneurial self-efficacy plays a complete mediating role between entrepreneurship education and entrepreneurial intention. Entrepreneurial self-efficacy also has a suppressing effect on the relationship between the two. (4) Entrepreneurial competition experience moderates the second half of the mediating effect of entrepreneurial self-efficacy. Finally, the study offers several proposals for the teaching practice of entrepreneurship education.